Non-performing Financing and Rate of Return on Mudharaba and Musharaka Contracts of Islamic Banks Before and During the COVID-19 Period - Fatoni, Ahmad; Siswati, Maidah; Utami, Kurnia Dwi Sari (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2024)
The purpose of this study is to evaluate whether there are differences in non-performing financing and yield rates on mudharaba and musharaka financing of Islamic commercial banks in Indonesia, both before and during the COVID-19 pandemic. This study uses a quantitative method using a sample of 14 Islamic commercial banks in Indonesia. The data used is monthly secondary data obtained from Islamic banking statistics for 2017-2022. Data analysis was carried out using the Kolmogorov-Smirnov Test normality test and the Wilcoxon Signed Rank Test non-parametric difference test using IBM SPSS 26 software. The results showed differences in non-performing financing and the rate of return on mudharaba and musharaka financing in the period before and during the COVID-19 pandemic.